ldcf.net
ǰλãҳ >> ΪʲôCos2x=1%2(sinx)^2 >>

ΪʲôCos2x=1%2(sinx)^2

cos2x=(cosx)^2-(sinx)^2 =1-(sinx)^2-(sinx)^2 =1-2(sinx)^2

ã cos(2x)=cos(x+x)=cosx*cosx-sinx*sinx=(cosx)^2-(sinx)^2=1-2(sinx)^2 شϣлл

cos(x+y)=cosxcosy-sinxsiny Ȼ Ƶ cos2x=cos(x+x) cos(x+x)=cosxcosx-sinxsinx=(cosx)^2-(sinx)^2 ϣﵽ㡣 ֻǸһѧд©ָ̡

⣺ cos2x=cos(x+x) =cosx*cosx-sinx*sinx =(cosx)^2-(sinx)^2 ʽӦõcos(x+y)=cosx*cosy-sinx*sinyx=y

cos2x=cos^2x-sin^2x=1-2sin^2x=2cos^2x-1 μ

ʵe^x1ȼxln(1+x)ȼxsinxȼx1(1+sinx)^x1e^(xln(1+sinx))1ȼxln(1+sinx)ȼxsinxȼx^22ش﷨(tanx)^xlim(tanx)^x=e^(limxlntanx)=e^(limlntanx/(1/x))e^(limsec^2x/tanx/(...

f(x)=cos2x+2sinx =1-2(sinx)^2 +2sinx =-2(sinx)^2 +2sinx+1 =-2[(sin)^2-sinx]+1 =-2[(sin)^2-sinx+1/4-1/4]+1 =-2[(sin)^2-sinx+1/4]++1/2+1 =-2(sinx-1/2)^2+3/2

## ̩չʽ ˼·ȫȷӦsinx̩չˣοͼ

f(sinx)=1+cos2x = 1+ (1-2(sinx)^2) = 2 - 2(sinx)^2 f(x) =2-2x^2 lim(x-> )(3x^3-7x+4)/(7x^3-8x+9) =lim(x-> )(3-7/x+4/x^3)/(7-8/x^2+9/x^3) =3/7

ͿsinxĶʽม ڣԳᣬȡֵΧ

վҳ | վͼ
All rights reserved Powered by www.ldcf.net
copyright ©right 2010-2021
磬ַϵͷzhit325@qq.com